The effects of isoflavones on bone density in postmenopausal women at tertiary centre - Singh, Neetu; Kumar, Dileep; Dubey, Preeti; Chandanan, Ani; Singh, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The objective of study was to study the effect of isoflavone supplement on bone density of postmenopausal women. Methods: Women aged 49–65 y (n = 205) were enrolled in a double-blind, prospective randomized, placebo-controlled trial; 177 completed the trial. Bone density, body composition, bone turnover markers and diet were measured at baseline and after 12 months. Results: Loss of lumbar spine bone mineral content and bone mineral density was significantly lower in the women taking the isoflavone supplement than in those taking the placebo. Interactions between treatment group and menopausal status with respect to changes in other outcomes were not significant. Conclusions: These data suggest that, through attenuation of bone loss, isoflavones have a potentially protective effect on the lumbar spine and femur neck in women.